Equivalent Damping Control of Radial Twist Motion for Permanent Magnetic Bearings Based on Radial Position Variation - Liu, Chao; Liu, Gang (IEEE transactions on industrial electronics (1982), 2015)
To effectively reject the influence of the low damping property of permanent magnetic bearings and improve the twist motion stability, this paper presents a novel equivalent damping control strategy. First, the relationship between the restoring torque and the radial translation of permanent magnetic rings is pointed out through finite-element analysis. The analysis indicates that the restoring torque increases with the radial translation of the rotor off its origin. Then, the radial translation variation rule is proposed, which can provide equivalent damping for the twist motion. Subsequently, a bang-bang controller is designed enlightened by the variation rule. Moreover, the stability of the bang-bang control is verified using energy consumption arguments, which is similar to the Lyapunov method. Finally, simulation and experimental results are presented to demonstrate the effectiveness of the proposed method.